HUBUNGAN ANTARA PENGGUNAAN WAKTU KUIS DAN NILAI KOGNITIF KUIS PADA PROSES PEMBELAJARAN TAKSONOMI VERTEBRATA - Mimin Mardhiah Zural; Nurhadi Nurhadi; Nadira Hanifah; Islahuddin Islahuddin (Fakultas Ilmu Pendidikan Universitas Negeri Surabaya, 2022)
Since practical lectures were only conducted online through various e-learning platforms for all subjects. Some issues accompanying an online learning include internet signal problem, internet packages data, power outage, weather conditions (rain and lightning), and geographic conditions which may cause internet signal disconnection. Worrying about these issues made the students feel uneasy during the lecturing process, including while doing quizzes and exams. This research aims to determine the degree and significance of the correlation between quiz time usage and cognitive score. The population was 67 students participating in the vertebrate taxonomy course of Biology Education Study Program of Universitas PGRI Sumatera Barat and the sample was determined randomly with the criteria for the frequency of participation in the quiz process through e-learning platform eight times. The research data in the form of the time used by students to do the quiz (X) and the average cognitive score of the quiz (Y) were analyzed correlationally. The results showed that there was a moderate and significant positive linear correlation between the time usage and the cognitive scores for the vertebrate taxonomy course. The contribution of quiz time to the cognitive score of the quiz was 53.3%. Keywords: Time Usage, Quiz, Cognitive Score and Vertebrate Taxonomy